2018
DOI: 10.1007/s00701-018-3549-1
|View full text |Cite
|
Sign up to set email alerts
|

Vasospasm-related complications after subarachnoid hemorrhage: the role of patients’ age and sex

Abstract: DRKS, Unique identifier: DRKS00008749.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
25
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 34 publications
(27 citation statements)
references
References 49 publications
2
25
0
Order By: Relevance
“…Arguably, a higher percentage of brain atrophy in older patients would explain the lower level of cerebral edema, thus accounting for our findings. Other indicators such as smoking, hypertension, diabetes mellitus, and hydrocephalus were not found to be significantly related to subsequent CI occurrence in our univariate analysis, which is in line with the results of previous studies that have not shown strong relationships of these factors with CI incidence [18,[21][22][23].…”
Section: Other Factors Influencing Ebi Resolutionsupporting
confidence: 91%
“…Arguably, a higher percentage of brain atrophy in older patients would explain the lower level of cerebral edema, thus accounting for our findings. Other indicators such as smoking, hypertension, diabetes mellitus, and hydrocephalus were not found to be significantly related to subsequent CI occurrence in our univariate analysis, which is in line with the results of previous studies that have not shown strong relationships of these factors with CI incidence [18,[21][22][23].…”
Section: Other Factors Influencing Ebi Resolutionsupporting
confidence: 91%
“…The following variables were collected from the institutional observational SAH database and in‐house electronic medical records: age; clinical grade on admission according to the World Federation of Neurosurgical Societies (WFNS) scale [22]; presence of ICH on initial CT; treatment modality; DC timing (primary/secondary) and type (BFCE/HCE); functional outcome at discharge and 6 months after SAH; and conservative ICP management before and after DC. All CT scans up to 6 weeks after SAH were reviewed by the first author (R.J.) for the occurrence of new cerebral infarctions [23].…”
Section: Methodsmentioning
confidence: 99%
“… 30 , 31 ) Although a recent 32 ) study reported that the aneurysm location did not affect the incidence of delayed cerebral infarction, female sex was reported to be an independent predictor of symptomatic vasospasm. 33 ) The present study had a significantly higher frequency of female patients with ICA aneurysms (ICA: 79.3% vs. others: 57.7%), and the high rate of DIND in ICA aneurysms may have been affected by these factors. In this study, we divided all the complications into two groups, namely, hemorrhagic and nonhemorrhagic complications, because we hypothesized that the increase of hematoma could induce vasospasm after radical treatment.…”
Section: Discussionmentioning
confidence: 48%